Employment rather than unemployment in a transitional rural formation - Karaşin, F. Banu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1984., 1984)
This study is an endeavour to develop a model of employment and/or unmployment so that it can adequatly be defined as both a theoretical and a social problem. For this end, the theoretical premise of a dynamic social totality and a certain structural causal model are adopted. Thus, while producing the new definition, employment is conceived of as an overdetermined social phenomenon. Accordingly, the employment process is analyticalIy broken down into three constituent determinants and/or aspects; theidnternal dynamics are elaborated to arrive at the general concep'tual description of each. It is argued that each aspect of employment involves different social practices founded on discrete levels of social reality. These in tum are generated by the contradictory but indispensable unity of elements embeded in each structural level. As a corollary, at the economic level, the production aspect of employment puts stress on the consequence of labour performance. At the political level, the income aspect of employment is concerned with renumeration of labour performance through the distribution of newly created value within the production process. Finally, at the ideological level, the recognition aspect of employment deals with the relation of the employed/unemployed to the lived world through labour performance in the form of selfconception vis-a-vis employmen t. The analysis proceeds historically when each aspect of employmentis discussed within an 'imaginary' context of a transitional rural formation. Here, the rural employment situation is elucidated in a (definite) time and (relatively indefinite) space matrix characterized by a specific form of capitalist penetration which subsumes other existing capitalist and non-capitalist modes of production. Theoretically, each determinant of employment also indicates one potential cause of unemployment. Emprically, the logical consequences of the suggested model can be used to 'quantify' unemployment. However, the tentative operationalization of these aspects may lead to the identification of a person's employment/unemployment status differently which depends on what determinant of employment he/she is subjected to testing. Therefore, the counterpart of employment can only be unemployment when a person is simultaneously ranked as unemployed in all aspects of employment. It has to be noted, furthermore, that the new concept of employment/unemployment developed in the present research is to be considered as a contribution towards the organization of thought, collection of data and formation of policies. It does not advocate a certain remedial strategy in combating unemployment although it has focused on the relevant dimensions of employment in a transitional rural formation where social policy can be effective. Nor, does it intend to establish a new discipline. Still, hopefully, it is designed to reveal that the range of social phon omena can be treated consistenty and more fruitfully over a common denominator. And this is realized on the basis of a definite methodology.
Keywords: Unemployment.; Labor supply.; Manpower policy, Rural.